Can optic nerve morphology in children with autism spectrum disorder be associated with atypical visual-sensory behaviors? - Tezcan, Mustafa Esad; Ataş, Abdullah Enes; Ferahkaya, Hurşit (Frontiers in Psychiatry, 2025)
IntroductionThe aim of this study is to investigate, using magnetic resonance imaging (MRI), the optic nerve diameter, morphometric characteristics of the optic chiasm (OC), volumes of the lateral, third, and fourth ventricles, as well as the volumes of the corpus callosum (CC) and choroid plexus (CP) in children with autism spectrum disorder (ASD), and to compare these findings with those of a typically developing (TD) control group. Additionally, the study seeks to evaluate the impact of these neuroanatomical parameters on autism symptom severity and sensory sensitivity.MethodsThis study included 111 children with ASD and 143 TD control children, aged between 5 and 13 years. The severity of ASD was assessed using the Social Communication Questionnaire (SCQ) and the Childhood Autism Rating Scale (CARS). Symptoms related to sensory sensitivities in ASD were evaluated using the Autism Behavior Checklist (AuBC).ResultsIn the ASD group, OC height, and the volumes of the CP and CC were significantly higher compared to the TD group, whereas OC width and third ventricular volume were significantly lower. There were no significant differences between the two groups in terms of optic nerve volumes, OC cross-sectional area, lateral and fourth ventricular volumes, or total brain volume. OC height was positively correlated with CARS, AuBC relationship, and AuBC use of body and objects scores, while OC width was positively correlated with CARS and AuBC use of body and objects scores. Conversely, OC height showed a negative correlation with AuBC personal-social development scores. After controlling for potential confounding variables such as total brain volume, age, and sex, the results of the covariance analysis remained unchanged. In multiple logistic regression analysis, left CP volume was found to be more strongly associated with ASD diagnosis compared to other morphometric measures.DiscussionThe findings of this study suggest that increased OC height, increased CC and CP volumes, and decreased third ventricular volume may play a role in the etiopathogenesis of altered brain development in children with ASD.